Andrographis paniculata Nees : a beneficial ingredient for herbal preparations - Wiart, C. (Forest Research Institute Malaysia (FRIM), 2015)
Andrographis paniculata Nees (Acanthaceae) is a famous Southeast Asian bitter medicinal herb. Its pharmacological and toxicological properties suggested that it could be an ideal candidate for herbal preparations. For example, A. paniculata has been found to be able to protect liver from toxins, reduce high blood pressure and prevent antherosclerosis. It also exerts greater antidiarrhoeal effect than loperamide (Imodium). In addition, double blind clinical studies have suggested that it could be useful in preventing colds. The present paper discusses the antimicrobial, antioxidant and antimotility properties of locally available A. paniculata.